A mediastinal inflammatory cyst due to gastric perforation containing organisms of Sarcina ventriculi. Issue 12 (December 2016) - Khan, Zanobia; Kalimuthu, Sangeetha N.; Tanguay, Jeffrey; Trainor, Shannon; Chetty, Runjan
Abstract: A patient presented with a mediastinal cyst and air in the thorax following gastric rupture. Within the mediastinal inflammatory pseudo-cyst, several curious but distinctive organisms of Sarcina ventriculi were observed. Sarcina is an anaerobic, spore-forming, Gram-positive coccus with a distinct morphology that can be recognized easily on light microscopy. Its pathogenicity in animals is well established in veterinary literature. However, its role as a pathogen in humans is not certain. S. ventriculi has been reported in asymptomatic patients as well as those with a clinical history of gastric stasis. It has a well-documented association with life-threatening complications such as emphysematous gastritis or esophagitis, gastric perforation and peritonitis. We report a case of S. ventriculi organisms within a secondary inflammatory cyst in a patient who presented with gastric perforation. The organisms are thought to be contaminants as a result of gastric contents being present within the mediastinal inflammatory cyst.